2021
DOI: 10.1111/raq.12528
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of salmon lice in response to management strategies: a review

Abstract: Ectoparasitic salmon lice (Lepeophtheirus salmonis) present a major challenge to Atlantic salmon (Salmo salar) aquaculture. The demand for effective louse control has produced diverse management strategies. These strategies essentially impose novel selection pressures on parasite populations, driving the evolution of resistance. Here we assess the potential for salmon lice to adapt to current prevention and control methods. Lice have evolved resistance to at least four of five chemical therapeutants, and use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 263 publications
(612 reference statements)
0
50
0
Order By: Relevance
“…Lice of all life stages face novel conditions and selection pressures at farms, including a high density and abundance of both hosts and conspecifics, along with periodic human intervention in the form of lice management (preventative or post-infestation delousing) and harvesting of their salmonid hosts. Coates et al (2021) assessed the potential for salmon lice to adapt to the main prevention and control methods (chemotherapeutants, mechanical and thermal treatments, cleaner fish, freshwater treatments, depth-based preventions [e.g. skirts and snorkels] and selective breeding).…”
Section: Implications For Salmon Lice Ecology and Evolutionmentioning
confidence: 99%
See 4 more Smart Citations
“…Lice of all life stages face novel conditions and selection pressures at farms, including a high density and abundance of both hosts and conspecifics, along with periodic human intervention in the form of lice management (preventative or post-infestation delousing) and harvesting of their salmonid hosts. Coates et al (2021) assessed the potential for salmon lice to adapt to the main prevention and control methods (chemotherapeutants, mechanical and thermal treatments, cleaner fish, freshwater treatments, depth-based preventions [e.g. skirts and snorkels] and selective breeding).…”
Section: Implications For Salmon Lice Ecology and Evolutionmentioning
confidence: 99%
“…skirts and snorkels] and selective breeding). Lice have evolved resistance to at least 4 of 5 chemical therapeutants (Aaen et al 2015, Myhre Jensen et al 2020, and while evidence is incomplete for the other louse control methods, Coates et al (2021) concluded that the evolution of resistance to non-chemical methods is a strong possibility given the variation that exists in and between louse populations (Jacobs et al 2018) on which non-chemical selection pressures could act and that this variation may have a genetic basis.…”
Section: Implications For Salmon Lice Ecology and Evolutionmentioning
confidence: 99%
See 3 more Smart Citations